PENGARUH METODE BERCERITA MENGGUNAKAN BIG BOOK TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN DI PAUD NATEZRA KID’S PASIR PUTIH KECAMATAN SIAK HULU - Silalahi, Remila Nurhaida; Utamai, Tri; Sari, Enda Puspita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this study are as follows: 1) To determine the listening skills of children aged 5-6 years in early childhood Natezra Kid's Pasir Putih Subdistrict Siak Hulu before the application of the method to tell by using a big book. 2) To determine the listening skills of children aged 5-6 years in early childhood Natezra Kid's Pasir Putih Subdistrict Siak Hulu after application of the method to tell by using a big book. 3) To determine the effect of the application of methods to tell by using a big book in listening skills in children aged 5-6 years in early childhood Kids Natezra Pasir Putih Subdistrict Siak Hulu. The population in this study group of children aged 5-6 years in early childhood Natezra Kid's white sands upstream Siak districts totaling 10 children. Then all the population of the research sample is 10 children consisting of six boys and four girls. Data collection techniques in research using observation. Data analysis techniques in this study is a t-test analysis techniques. The survey results revealed that the method of storytelling using a big book could affect the listening skills of children aged 5-6 years in early childhood Natezra kid's white sand Siak Hulu subdistrict. The magnitude of the effect of storytelling using a big book on the listening skills of children amounted to 68.6%.Keywords: method of storytelling, big book, listening